ANALISIS REAKSI PASAR TERHADAP PENGUMUMAN RIGHT ISSUE PADA PERUSAHAAN GO PUBLIC YANG TERCATAT DI BEI - Paramita Apsari, Ida Ayu Wiasti; Wirawan Yasa, Gerianta (E-Jurnal Akuntansi, 2017)
The announcement of the rights issue carried out to see the market reaction to the announcement and know their abnormal return or around the period of announcement of right issue. This research was conducted in the Indonesia Stock Exchange with a total sample of 73 companies went public and 90 announcement of right issue, using non-probability sampling method that consists of companies that conduct the rights issue announcement in the 2011-2015 period. Data collection method used was non-participant observation method. From the research carried out can be concluded that there is a negative market reaction on the third day prior to the announcement of the rights issue and at the time of the announcement of the rights issue there is no market reaction , while there are positive market reaction on the first day and the fourth day after the announcement of the rights issue.
Keywords: Market Reaction, Right Issue, Abnormal Return